Il ritorno dell’ordoliberalismo in Europa - Massimo Pendenza (Quaderni di Sociologia)
A distinction must be made between the neoliberalism of the 1970s, an expression of the economic principles of the Vienna and Chicago Schools, and that of the Ordoliberals, economists and jurists of the Freiburg School, active since the 1930s in Germany, then of its postwar reconstruction and finally of the European economic model. Intertwined since the Lippmann Conference in 1938, the two currents, while agreeing on the establishment of a competitive economic order, nevertheless have always held different views on the functioning of the economy. The aim of the article is to show the major divergences between the two variants of neoliberalism (and between the Viennese and the Chicagoans), as well as to demonstrate that the economic governance of the European Union rests more on the latter than on the former, to the extent that today one could speak, especially after the 2008 financial crisis, of the ordoliberalization of Europe.